2012
DOI: 10.2169/internalmedicine.51.7193
|View full text |Cite
|
Sign up to set email alerts
|

Severe Steroid-resistant Thrombocytopenia Secondary to Cytomegalovirus Infection in an Immunocompetent Adult

Abstract: Severe thrombocytopenia secondary to cytomegalovirus (CMV) infection is rare in immunocompetent hosts. We describe a case of severe thrombocytopenia secondary to CMV infection in an immunocompetent 30-year-old man who presented with pyrexia and bleeding tendency. A diagnosis of immune thrombocytopenia (ITP) was made following hematological and serological testing, and bone marrow aspiration. Acute CMV infection was confirmed by serological testing, antigenemia, and detection of CMV-DNA. Corticosteroid therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…After excluding reports on immunocompromised patients or other CMV‐related disorders (e.g., thrombotic microangiopathies, haemophagocytic syndrome, etc. ), 25 cases described in 23 articles 5,9–30 that had been published between 1973 and 2016 remained. Five previously unreported cases from three Israeli medical centres were identified in the database searches.…”
Section: Resultsmentioning
confidence: 99%
“…After excluding reports on immunocompromised patients or other CMV‐related disorders (e.g., thrombotic microangiopathies, haemophagocytic syndrome, etc. ), 25 cases described in 23 articles 5,9–30 that had been published between 1973 and 2016 remained. Five previously unreported cases from three Israeli medical centres were identified in the database searches.…”
Section: Resultsmentioning
confidence: 99%
“…Aoki et al reported a case with a platelet count of 17,000 /μL ( 13 ), which was slightly higher than the present case (9,000 /μL). Acute CMV infection may also result in thrombocytopenia ( 14 , 15 ), which may have had a negative impact on the patient's degree of thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…The use of systemic corticosteroids is an alternative choice for the treatment of thrombocytopenia induced by either HIV or CMV. However, there have been reports that demonstrate only a partial response or no response ( 13 , 14 ). In addition, steroid use is reported to be independently associated with the development of CMV colitis in immunocompetent hosts ( 19 ).…”
Section: Discussionmentioning
confidence: 99%